New directions in the study of work and employment: revitalizing industrial relations as an academic entreprise (Cheltenham, 2008)
"Charles Whalen's book identifies avenues leading to the revitalization of industrial relations as an academic discipline. The contributors, a stellar assemblage of the field's leading scholars, demonstrate there is much work to be done: the scope and intellectual content of industrial relations need to be reconsidered; academic and social institutions must be reshaped; and, new conceptual and practical issues demand attention. The authors of the present volume examine a broad range of issues.Some chapters in this book explore the conceptual boundaries and core assumptions of the field; others examine topics including industrial relations law, social capital and industrial relations institutions, changes to the field's academic curricula, the impact of the structure of academic departments on industrial relations scholarship, the state of labor and employment journals, and new approaches to the integration of teaching and community service. There is a wrap-up chapter by MIT's Thomas Kochan that ties all this together and presents additional insights on the revitalization of the field. Industrial relations scholars, labor studies, sociology and business professors as well as many practitioners will find much to recommend in this book."